Validity and reliability of an instrument in Portuguese to assess bicycle use patterns in urban areas - Marilson Kienteka; Rodrigo S Reis (Universidade Federal de Santa Catarina, 2017)
The aim of this study was to analyze the validity and reliability of an instrument to assess bicycle use patterns in urban areas through systematic observation. The instrument items were selected from a literature review. Content validity was established by consensus opinion of experts of the physical activity area. The temporal stability (reliability) was verified by percentage of agreement and intraclass correlation coefficient (ICC). Observations were conducted using an adapted protocol based on the System for Observing Play and Recreation in Communities (SOPARC), consisting of systematic scans for counting cyclists in an urban area through video images provided by the public transport control system of Curitiba (URBS). Observers A and B recorded a total of 383 and 378 cyclists. Most of the observed subjects were men (87%), adults (84%), cycling on the BRT lane (54%), coming from downtown (54%), rode the bicycle on the wrong side of the street (58.2%), were not wearing a helmet (76.8) and bicycled alone (64%). Agreement percentiles ranged from 89.2 to 99.5% and ICC values from 0.922 to 0.999. According to criteria adopted, reliability was considered high in all categories included in the instrument. The instrument showed validity and reliability to be used in studies aiming to evaluate bicycle use patterns in Brazilian urban areas.